2010
DOI: 10.2174/1874381101003010001
|View full text |Cite
|
Sign up to set email alerts
|

The Perihelion Precession of Saturn, Planet X/Nemesis and MOND~!2009-09-17~!2009-10-08~!2010-05-05~!

Abstract: Abstract:We show that the anomalous retrograde perihelion precession of Saturn !& " , recently estimated by different teams of astronomers by processing ranging data from the Cassini spacecraft and amounting to some milliarcseconds per century, can be explained in terms of a localized, distant body X, not yet directly discovered in the remote periphery of the solar system. From the determination of its tidal parameter K ! GM X / r X 3 as a function of its ecliptic longitude X ! and latitude X ! , we calculate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…[32] has put forth a different form for the planetary EFE yielding an additional quadrupolar extra-acceleration which mimics the action of distant mass; some consequences have been investigated in Ref. [33].…”
Section: The External Field Effect In Mondmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] has put forth a different form for the planetary EFE yielding an additional quadrupolar extra-acceleration which mimics the action of distant mass; some consequences have been investigated in Ref. [33].…”
Section: The External Field Effect In Mondmentioning
confidence: 99%
“…For other works on MOND in the inner regions of the solar system, see Ref. [4,22,23,24,25,26,27,28,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…= GM X /r 3 X according to the anomalous perihelion precession of Saturn analyzed in Ref. 40 a genuine physical effect h . The maximum effect of X on the Mercury range would be as large as 1.5 − 3 m, falling within the measurability domain of BepiColombo.…”
Section: Planet Xmentioning
confidence: 97%
“…• Iorio (2010) found that a distant, pointlike massive object in the outer regions of the solar system may explain the anomalous retrograde precession 1 of the perihelion of Saturn preliminarily estimated (Pitjeva 2008) by analyzing some radiotechnical data points from the Cassini spacecraft exploring the Saturnian system.…”
Section: Introductionmentioning
confidence: 98%
“…Have not the remote peripheries of the solar system saved any further big surprises for us? It is a long time (Lowell 1915;Pickering 1928Pickering , 1931Schuette 1949) that such questions−still well alive (Lykawka and Mukai 2008;Iorio 2010;Matese and Whitmire 2011;Fernández 2011)−are well rooted in the astronomical community, having often resurfaced in different contexts and with changed forms;. For a recent, popular review, see Schilling (2009).…”
Section: Introductionmentioning
confidence: 99%